Catalytic Pyrolysis of Polypropylene Using Nickel Supported Sago Waste Activated Carbon for Liquid Fuel - Syukrika Putri; Nurmalasari Nurmalasari; Suci Ramadani; Dian Safitri (Universitas Darul Ulum, 2026)
The catalytic pyrolysis of polypropylene (PP) has attracted considerable attention as a promising approach for converting plastic waste into valuable fuels; however, the development of low-cost and sustainable catalysts remains a major challenge. In this study, the catalytic pyrolysis of polypropylene was conducted to investigate the effect of nickel supported on activated carbon (Ni/AC) derived from sago waste on liquid yield and hydrocarbon selectivity. Pyrolysis experiments were performed at 500 °C using catalyst loadings of 2.5 g, 5 g, and 7.5 g, alongside a non-catalytic run for comparison. The introduction of Ni/AC significantly enhanced liquid production compared to thermal pyrolysis, with the optimum yield achieved at moderate catalyst loading. Gas Chromatography–Mass Spectrometry (GC–MS) analysis confirmed that the liquid fraction was mainly composed of hydrocarbons in the gasoline (C₅–C₁₂) and diesel (C₁₃–C₂₀) ranges. Higher catalyst loading promoted secondary cracking, shifting selectivity toward gaseous products. These findings demonstrate that Ni/AC catalysts from sago waste provide an effective and sustainable approach for converting plastic waste into fuel-like hydrocarbons, underscoring their potential role in plastic waste valorization and sustainable energy development.